PRELIMINARY ANALYSIS OF PUBLIC ARCHIVES ADMINISTRATION TASKS IN MALAYSIA BASED ON THE NATIONAL ARCHIVES ACT 2003 (ACT 629) - Ahmad Azman Mohamad Ramli; Noor Faraliza Samsudin; Intan Nurbaizura Zainuddin; Mohd Naim Mohd Nasfi; Norhidayu Md Yatim; Seri Intan Idayu Shahrul Asari; Razifah Othman; Kasmarini Baharuddin (INTERNATIONAL JOURNAL OF LAW, GOVERNMENT AND COMMUNICATION (IJLGC), 2025)
The National Archives Act 2003 (Act 629) is an act enacted to ensure that public archives in Malaysia can be administered well to ensure that this valuable source of information is always safe, accessible and used for reference by current and future researchers. Among the provisions in this act are those related to the tasks that need to be carried out to ensure that the public archives can always be administered well. In this regard, the objective of this paper is to analyze the question of what the tasks and their characteristics are. The method used to achieve this objective is to use the literature review method on the content of information sources such as the National Archives Act 2003 (Act 629), reference books, articles, acts and other related regulations. Based on this analysis, it was found that there are four public archives administration tasks as stipulated by this act. The names of the four tasks are the processing and preservation of public archives, access to public archives, access to classified archives and prohibition on reproduction and publication of public archives. The characteristics of each of these tasks are discussed in this paper. It is hoped that the results of this analysis will contribute to increasing the reader’s knowledge of the administrative tasks of public archives in Malaysia and their characteristics as stipulated by the National Archives Act 2003 (Act 629). It is also hoped that the findings from this analysis will be able to catalyze more in-depth study related to the administrative tasks of this very valuable information source of our nation in the future.